Diogenes Laertius and women philosophers - Bonelli, Maddalena (Revista Archai, 2025)
This article focuses on one of the primary ancient sources for reconstructing lives and opinions of women philosophers in antiquity: Diogenes Laertius. It aims to demonstrate that Diogenes provides portraits of women wich should be included in the philosophical canon and studied as part of the history of philosophy.